Առաջին համաշխարհային պատերազմի զոհերի վերաիմաստավորումը Ռ.Օյրինգերի «Գերմանիայի չարչարանքները 1933» թինգշփիլում - Գոհար Փանոսյան (ՀՀ ԳԱԱ հրատ.)
На примере тингшпиля Р. Ойрингера “Мучения Германии 1933” статья показывает смысл жертв Первой мировой войны, а также жертвоприношений для нацистского режима. Статья также разъясняет функцию жертвоприношений и “культа мертвецов” в нацистской идеологии. R. Euringer in his article “Passion of Germany 1933”, making use of Thingspiel as an example, portrays the importance of the casualties of the First World War as well as the substance of sacrifice for the Nazi regime. It also clarifies the significance and magnitude of the role “the practice of sacrifice” and “worshiping of the dead” execute in the Nazi ideology.
Keywords: Language and Literature